Resonant magnetoabsorption of millimeter-wave radiation in the quasi-two-dimensional organic metals alpha -(BEDT-TTF)2MHg(SCN)4 (M=K,Tl). - Demishev, S; Semeno, A; Sluchanko, N; Samarin, N; Voskoboinikov, I; Glushkov, V; Singleton, J; Blundell, S; Hill, S; Hayes, W; Kartsovnik, M; Kovalev, A; et al. (1996)
The magnetoabsorption of millimeter-wave radiation by single crystals of the organic metals α-(BEDT-TTF)2TlHg(SCN)4 and α-(BEDT-TTF)2KHg(SCN)4 has been studied in the frequency range 30-120 GHz. The experiments reveal two dominant contributions to the magnetoabsorption spectra. The first is interpreted as the cyclotron resonance of two-dimensional carriers, and is characterized by broad lines (linewidth/magnetic field ΔB/B∼0.5-1). In addition to a resonance exhibiting a cyclotron mass mc∼2.8m0, there are two further lines corresponding to frequency-dependent cyclotron masses in the ranges mc∼(1-1.5)m0 and mc∼(0.5-0.8)m0. This frequency dependence is believed to result from many-body effects. The second contribution to the magnetoabsorption is formed by a series of narrow lines with ΔB/B∼0.03-0.1 and amplitudes 5-10 times smaller than the features interpreted as cyclotron resonances. These narrow lines are attributed to a superposition of modes due to antiferromagnetic resonance and conduction-electron-spin resonance (ESR). The feature characteristic of antiferromagnetic resonance is the presence of a mode with a frequency that decreases with increasing magnetic field. The magnetoabsorption structure attributed to ESR consists of a relatively broad maximum upon which a sharp dip is superimposed. This behavior is believed to be analogous to the resonant transparency observed in thin metallic films undergoing ESR.